Effect of Supplementation Garlic Powder (Allium sativum) in the Growth Parameters of Sahiwal Calves - Sorang, Zara Kaku; Deka, Raj Jyoti; Baruah, Dilip Kumar; Hussain, Jakir; Saikia, Gunaram; Shome, Arijit; Kaushik, Purabi (International Journal of Bio-resource and Stress Management, 2023)
The present experiment was conducted at Sahiwal Cattle Farm, College of Veterinary Science, Assam Agricultural University, Khanapara, Guwahati, Assam, India for a period of 120 days from July to November, 2022. to investigate the effect of supplementing garlic powder (Allium sativum) on the performance of Sahiwal calves. Twelve healthy Sahiwal calves of both sexes of similar age and body weight were allocated to two experimental groups, control and treatment with six animals in each group. Calves of both groups were fed with a standard basal diet consisting of concentrate, green fodder, and paddy straw. While in the treatment group, garlic powder was supplemented @ 250 mg kg-1 body weight along with concentrate feed. The experiment was conducted as a feeding trial for eight fortnights and a digestibility trial thereafter for five days in the two experimental groups. The statistical analysis revealed a highly significant differences (**p<0.01) in body weight of the calves, fortnightly body weight gains up to 8th fortnight and the dry matter intake of the calves. Statistical analysis also revealed highly significant (**p<0.01) differences in the conformation traits when compared between the groups with highly positive correlation with the body weight of the calves. Further it can be concluded that the supplementation of garlic powder at dosage of 250 mg kg-1 body weight in the Sahiwal calf ration is beneficial in terms of body weight gain, feed conversion ratio, body confirmation traits, and economic of feeding.